Transcriptional and Mutational Profiling of an Aminoglycoside-Resistant Pseudomonas aeruginosa Small-Colony Variant - Schniederjans, Monika (Antimicrob Agents Chemother, 2017)
Pseudomonas aeruginosa is a major causative agent of both acute and chronic infections. Although aminoglycoside antibiotics are very potent drugs against such infections, antibiotic failure is steadily increasing mainly because of increasing resistance of the bacteria. Many molecular mechanisms that determine resistance, such as acquisition of genes encoding aminoglycoside-inactivating enzymes or overexpression of efflux pumps, have been elucidated. However, there are additional, less well-described mechanisms of aminoglycoside resistance. In this study, we profiled a clinical tobramycin-resistant P. aeruginosa strain that exhibited a small-colony variant (SCV) phenotype. Both the resistance and colony morphology phenotypes were lost upon passage of the isolate under rich medium conditions. Transcriptional and mutational profiling revealed that the SCV harbored activating mutations in the two-component systems AmgRS and PmrAB. Introduction of these mutations individually into type strain PA14 conferred tobramycin and colistin resistance, respectively. However, their combined introduction had an additive effect on the tobramycin resistance phenotype. Activation of the AmgRS system slightly reduced the colony size of wild-type PA14, whereas the simultaneous overexpression of gacA, the response regulator of the GacSA two-component system, further reduced colony size. In conclusion, we uncovered combinatorial influences of two-component systems on clinically relevant phenotypes such as resistance and the expression of the SCV phenotype. Our results clearly demonstrate that the combined activation of P. aeruginosa two-component systems has pleiotropic effects with unforeseen consequences.